Pendampingan Product Branding melalui Pengembangan Website dan Instagram bagi Pengrajin Eceng Gondok di Kabupaten Garut - Kusmiati, Eti; Nurbudiwati, Nurbudiwati; Fakhrun Shiddieq, Diqy (Universitas Galuh, 2024)
Water hyacinth craftsmen must prioritize product branding through websites and Instagram to construct a strong product image, captivate consumer attention, and extend their market reach. The primary aim of the service is to assist water hyacinth craftsmen in broadening their market and enhancing product accessibility through the development of websites and strategic use of Instagram for social media marketing. The specific focus is on the Waluya Mukti Sejahtera water hyacinth craftsmen group in Sukamukti Village, Banyuresmi District, Garut Regency. The service encompasses rigorous training and mentoring to effectively develop websites and leverage Instagram for social media marketing. The impact of this service has been substantial, as the craftsmen now recognize the indispensable nature of websites and Instagram as powerful branding tools for improving product visibility, establishing business credibility, and fostering consumer trust.